Co-Application of Tetramycin and Matrine Improves Resistance of Kiwifruit against Soft Rot Disease and Enhances Its Quality and Amino Acids - Cheng Zhang; Wenzhi Li; Youhua Long; Yue Su; Qinghai Zhang (MDPI AG, 2022)
Soft rot disease caused by Botryosphaeria dothidea and Phomopsis sp. is the most serious fungal disease of the kiwifruit production area in southwest China. In this work, the role of the co-application of tetramycin and matrine in the resistance of kiwifruit fruits against soft rot disease and its effects on development, quality and amino acids of kiwifruit fruits were investigated. The results indicate that matrine exhibited an outstanding toxicity against B. dothidea RF-1 and Phomopsis sp. RF-2 with EC50 values of 0.442 and 0.332 mg kg−1. The foliar co-application of 0.3% tetramycin aqueous solutions (AS) 5000-fold liquid + 0.5% matrine AS 1000-fold liquid could effectively control soft rot disease with a control efficacy of 82.68%, which was significantly (p < 0.05) higher than 75.19% of 0.3% tetramycin AS 5000-fold liquid and significantly (p < 0.01) higher than 68.50% of 0.5% matrine AS 500-fold liquid. Moreover, the co-application of tetramycin and matrine was more effective than tetramycin or matrine alone in improving disease resistance, quality and amino acids of kiwifruit fruits. This study highlights that the co-application of tetramycin and matrine can be used as a practicable, cost-effective and environmentally friendly candidate or alternative approach for controlling soft rot disease of kiwifruit.